Lepus (Lepus) timidus subsp. timidus Linnaeus 1758 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lepus (Lepus) timidus subsp. timidus Linnaeus 1758 Lepus (Lepus) timidus subsp. timidus Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 57. Type Locality: "in Europa" [Uppsala, Sweden]. Synonyms: Lepus (Lepus) timidus subsp. abei Kuroda 1938; Lepus (Lepus) timidus subsp. alpinus Erxleben 1777; Lepus (Lepus) timidus subsp. algidus Pallas 1778; Lepus (Lepus) timidus subsp. borealis Pallas 1778; Lepus (Lepus) timidus subsp. canescens Nilsson 1844; Lepus (Lepus) timidus subsp. collinus Nilsson 1831; Lepus (Lepus) timidus subsp. septentrionalis Link 1795; Lepus (Lepus) timidus subsp. sylvaticus Nilsson 1831; Lepus (Lepus) timidus subsp. typicus Barrett-Hamilton 1900; Lepus (Lepus) timidus subsp. variabilis Pallas 1778. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Lagomorpha, pp. 185-211 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 204, DOI: 10.5281/zenodo.7316519